Baseline lung function, exercise-induced bronchoconstriction, and asthma-like symptoms in elite women ice hockey players - Rundell, K. W.; Spiering, B. A.; Evans, T. M.; Baumann, J. M. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: Exercise-induced bronchoconstriction (EIB) is high among ice rink athletes and may be related to exercise ventilation of rink air pollutants. Impaired postchallenge expiratory flows are common for this population; however, baseline lung function and symptoms have not been fully evaluated. METHODS: We examined resting lung function and asthma-like symptoms in relation to airway hyperresponsiveness in National Team female ice hockey players (N = 43). Subjects were grouped according to observed symptoms and medical history as symptomatic ('S') or asymptomatic ('A'). Baseline and postexercise lung function was determined. RESULTS: Seventeen (39.5%) presented symptoms and 9 (21%) had EIB. Baseline FEV1, FEV1/FVC, and FEF25-75 were different between 'S' and 'A' (102 +/- 14% vs 116 +/- 12%, 77.7 +/- 7.5 vs 88.2 +/- 4.5, and 74 +/- 22% vs 118 +/- 24%, respectively; P < 0.05); FVC and PEF were not different. Ten 'S' athletes had <80% FEV1/FVC; 9 had <70% predicted FEF25-75. Six of 9 EIB+ subjects had symptoms; cough occurred in all six and was related to EIB (chi 2 = 4.23, OR = 6.5, CI = 1.1-44.1; P = 0.039). CONCLUSION: Baseline lung function is related to symptoms and precludes EIB in some rink athletes, suggesting that EIB and its development is a heterogeneous and may involve fibrotic as well as inflammatory processes. Small airway dysfunction in ice arena athletes is likely related to internal combustion pollutants emitted from ice resurfacing machines.